Peran Orang Tua Dalam Pendidikan Anak Pada Keluarga Petani Di Desa Mekar Baru - Rahayu, Yulia (UNIVERSITAS TANJUNGPURA, 2014)
The purpose of this study to determine the role of parents in the education of children in a family of farmers in the village of New Blooms Kingdom River District Kubu Raya district. The method used in this study uses qualitative research with descriptive methods. While the data collection tool used was observation, interview and documentation. The results can be concluded: Modeling pretty good parents because parents in their daily faith educating intellectual education, psikhis education, and social education. Parental guidance is categorized well, because parents try to pay attention and keep an eye on children's education and motivation of the parents pretty well because parents encourage children to be more.Keywords : Role Of Parents, Children's Education, Family Farmers.